Asymptotic stability of periodic solutions for a nonlinear neutral first-order differential equation with functional delay - Makhzoum, Haitham; Elmabrok, Abdelhamid (Libyan Journal of Science &Technology, 2022)
We consider the nonlinear neutral differential equation and use the contraction mapping principle to show the asymptotic stability of the zero solution provided that